Effects of sunshades on temperature and cow comfort - John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1994)
Sunshades provide an effective method of reducing ultraviolet sunrays and increasing cow comfort.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Sunshades; Environmental temperature; Cow comfort